2013
DOI: 10.1089/scd.2012.0623
|View full text |Cite
|
Sign up to set email alerts
|

Ddx46 Is Required for Multi-Lineage Differentiation of Hematopoietic Stem Cells in Zebrafish

Abstract: Balanced and precisely controlled processes between self-renewal and differentiation of hematopoietic stem cells (HSCs) into all blood lineages are critical for vertebrate definitive hematopoiesis. However, the molecular mechanisms underlying the maintenance and differentiation of HSCs have not been fully elucidated. Here, we show that zebrafish Ddx46, encoding a DEAD-box RNA helicase, is expressed in HSCs of the caudal hematopoietic tissue (CHT). The number of HSCs expressing the molecular markers cmyb or T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…In this current study, the genomewide analysis revealed that 17 putative genes involved in spermatogenesis, embryogenesis, and innate immune were under positive selection; these genes encode for DDX46 , TAB1 , EIF2AK2 , AOAH , FLT3 , ZNF335, and IL9R (Figure ). For instance, DDX46 encodes a member of the DEAD box protein family, and some members of this family are believed to be involved in embryogenesis, spermatogenesis, and cellular growth and division (Hirabayashi, Hozumi, Higashijima, & Kikuchi, ). TAB1 plays an important role in mammalian embryogenesis (Komatsu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this current study, the genomewide analysis revealed that 17 putative genes involved in spermatogenesis, embryogenesis, and innate immune were under positive selection; these genes encode for DDX46 , TAB1 , EIF2AK2 , AOAH , FLT3 , ZNF335, and IL9R (Figure ). For instance, DDX46 encodes a member of the DEAD box protein family, and some members of this family are believed to be involved in embryogenesis, spermatogenesis, and cellular growth and division (Hirabayashi, Hozumi, Higashijima, & Kikuchi, ). TAB1 plays an important role in mammalian embryogenesis (Komatsu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, DDX46 encodes a member of the DEAD box protein family, and some members of this family are believed to be involved in embryogenesis, spermatogenesis, and cellular growth and division (Hirabayashi, Hozumi, Higashijima, & Kikuchi, 2013). TAB1 plays an important role in mammalian embryogenesis (Komatsu et al, 2002).…”
Section: Putative Selection Pressures On Reproduction Developmentmentioning
confidence: 99%
“…In vitro studies have shown that DDX46 plays an essential role in pre-mRNA splicing before or during prespliceosome assembly (Dalbadie-McFarland and Abelson, 1990;Ruby et al, 1993;Xu et al, 2004;Xu and Query, 2007;Kosowski et al, 2009). Additionally, in vivo zebrafish studies have shown that DDX46 is required for multi-lineage differentiation of hematopoietic stem cells (Hirabayashi et al, 2013) and the development of the digestive organs and brain (Hozumi et al, 2012). However, whether DDX46 is expressed and plays a role in cancer progression in humans has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…U2 snRNP is a large macromolecular complex made up of nearly 20 factors. Zebrafish mutants of three of these factors ( sf3a3 15 , ddx46/prp5 12 , and now sf3b1) have been characterized, and all display defects in the hematopoietic system. Mutants in sf3a3 have normal primitive erythropoiesis and myelopoiesis, but show defects in HSPC formation, while ddx46 mutants initiate HSPC induction normally, but have problems maintaining their stem cell pool.…”
Section: Discussionmentioning
confidence: 99%